Gaussian multiterminal source coding - Oohama, Y. (IEEE transactions on information theory, 1997)
In this paper, we consider the problem of separate coding for two correlated memoryless Gaussian sources. We determine the rate-distortion region in the special case when one source provides partial side information to the other source. We also show that the previously obtained inner region of the rate-distortion region is partially tight. A rigorous proof of the direct coding theorem is also given.